Resistance cost of a cytochrome P450 herbicide metabolism mechanism but not an ACCase target site mutation in a multiple resistant Lolium rigidum population - Vila-Aiub, M M (The New phytologist, 2005)
Costs of resistance are predicted to reduce plant productivity in herbicide-resistant weeds. Lolium rigidum herbicide-susceptible individuals (S), individuals possessing cytochrome P450-based herbicide metabolism (P450) and multiple resistant individuals possessing a resistant ACCase and enhanced cytochrome P450 metabolism (ACCase/P450) were grown in the absence of mutual plant interaction to estimate plant growth traits. Both P450 and ACCase/P450 resistant phenotypes produced less above-ground biomass than the S phenotype during the vegetative stage. Reduced biomass production in the resistant phenotypes corresponded to a reduced relative growth rate and a lower net assimilation rate and rate of carbon fixation. There were no significant differences between the two resistant phenotypes, suggesting that costs of resistance are associated with P450 metabolism-based resistance. There were no differences in reproductive output among the three phenotypes, indicating that the cost of P450 resistance during vegetative growth is compensated during the production of reproductive structures. The P450-based herbicide metabolism is shown to be associated with physiological resistance costs, which may be manipulated by agronomic management to reduce the evolution of herbicide resistance